Biomimetic cartilage scaffold with orientated porous structure of two factors for cartilage repair of knee osteoarthritis - Jianhua Wang; Yingying Wang; Xiaomin Sun; Deshuai Liu; Chenguang Huang; Jiulin Wu; Chunrong Yang; Qiqing Zhang (Artificial Cells, Nanomedicine, and Biotechnology)
A dual-layer biomimetic cartilage scaffold was prepared by mimicking the structural design, chemical cues and mechanical characteristics of mature articular cartilage. The surface layer was made from collagen (COL), chitosan (CS) and hyaluronic acid sodium (HAS). The transitional layer with microtubule array structure was prepared with COL, CS and silk fibroin (SF). The PLAG microspheres containing kartogenin (KGN) and the polylysine-heparin sodium nanoparticles containing TGF-β1 (TPHNs) were constructed for the surface, transitional layer, respectively. The SEM result showed that the dual-layer composite scaffold had a double structure similar to natural cartilage. The vitro biocompatibility experiment showed that the biomimetic cartilage scaffold with orientated porous structure was more conducive to the proliferation and adhesion of BMSCs. A rabbit KOA cartilage defect model was established and biomimetic cartilage scaffolds were implanted in the defect area. Compared with the surface layer and transitional layer scaffolds group, the results of dual-layer biomimetic cartilage scaffold group showed that the defects had been completely filled, the boundary between new cartilage and surrounding tissue was difficult to identify, and the morphology of cells in repair tissue was almost in accordance with the normal cartilage after 16 weeks. All those results indicated that the biomimetic cartilage scaffold could effectively repair the defect of KOA, which is related to the fact that the scaffold could guide the morphology, orientation, and proliferation and differentiation of BMSCs. This work could potentially lead to the development of multilayer scaffolds mimicking the zonal organization of articular cartilage.